Development of an UHPLC-MS/MS method for remifentanil quantification in a small plasma volume. Issue 15 (2nd October 2019) - O'Hara, Kate; Schneider, Jennifer J.; Jones, Alison L.; Wright, Ian M. R.; Martin, Jennifer H.; Galettis, Peter
Abstract: Remifentanil is a short acting opioid currently used in anesthesia and as an analgesic. This paper describes a simple, fast HPLC-MS/MS methodology that allows detection of remifentanil in low volume plasma samples. Acetonitrile protein precipitation is used for sample extraction and clean up. The assay has a lower limit of detection of 0.25 ng/mL and a 3 min run time. Graphical Abstract: